The Roberts–2: Italian Validation on a Sample of Children and Adolescents. Issue 3 (3rd May 2020) - Parolin, Laura; De Carli, Pietro; Locati, Francesca
Abstract: The Roberts–2 (Roberts & Gruber, 2005 ) is a narrative test that was specifically designed to assess developmental and clinical functioning in children and adolescents. It was developed with the intent of addressing the lack of objective scoring systems for narrative instruments to assess childhood. The Roberts–2 is characterized by a standardized administration, scoring system, and interpretation guidelines that use a performance-based approach to narrative testing. This instrument has gained wide recognition in clinical practice but is minimally supported by empirical literature. This study aims to decrease this gap between clinical application and research findings through the Italian validation of the Roberts–2. The Italian version of the Roberts–2 was validated in both nonclinical and clinical participants. Study 1 ( N  = 738) assessed an Italian community sample to validate the Roberts–2. Specifically, interrater reliability, factorial structure, and developmental trends were explored. In Study 2, we compared a community sample with a sample of clinically referred children ( N  = 86) to test the clinical significance of the Roberts–2 indexes. The test performed well in differentiating between developmental groups as well as between clinical and nonclinical samples. The test is a useful tool for assessing both developmental and clinical aspects of the psychological functioning of children and adolescents.